Hemichorea in ketotic hyperglycemia with hyperdense striatum mimicking hemorrhagic transformation in a patient using apixaban - Mikulenka, Petr; Stetkarova, Ivana (Neuro-endocrinology letters, 2020)
INTRODUCTION: Diabetic striatopathy is a rare condition characterized by unilateral hemichorea and/or hemiballismus in the settings of uncontrolled nonketotic diabetes mellitus. Imaging studies usually reveal striatal abnormality - subtle hyperdensity on CT and T1 hyperintensity on MRI. The resolution of clinical symptoms is prompt when optimal glycaemic control is achieved. CASE REPORT: We present the case of a 90-year-old male who came to our attention for acute involuntary choreiform movements of his left-sided extremities lasting two-weeks. Apart from that neurological examination was unremarkable. His medical history included hypertension, atrial fibrillation, previous stroke with no residual disability and poorly controlled type 2 diabetes mellitus on metformin treatment. There was no history of movement disorders or exposure to neuroleptics. His glucose level on admission was 512.6 mg/dL, glycated hemoglobin was 14%. CT scan of the head demonstrated an abnormally increased intensity within the right striatum. Treatment consisted of symptomatic treatment of chorea and improvement of blood glucose control. Tiapride was started with a dose of 100 mg 4 times a day. The patient was initiated on intensive insulin therapy which included insulin glargine 10 units every evening and 12 units of insulin glulisine 3 times a day with meals. Abnormal movements resolved after normoglycemia was achieved approximately 7 days after admission. Though striatal hyperdensity was still present at follow-up CT scan after 10 days, it was less pronounced. CONCLUSION: Diabetic striatopathy is a rare but treatable disorder and should be considered in patients with poorly controlled diabetes who present with hemichorea.
Keywords: pyrazoly; Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; Stroke; ketosy; Pyridones; chorea; Chorea; lidé; hyperglykemie; Ketoses; Diabetes Mellitus, Type 2; Hyperglycemia; cévní mozková příhoda; Male; Aged, 80 and over; pyridony; senioři nad 80 let; mužské pohlaví; Pyrazoles; diabetes mellitus 2. typu